Preliminary conceptual model of the Cerro Blanco caldera-hosted geothermal system (Southern Puna, Argentina): Inferences from geochemical investigations. (October 2019) - Chiodi, A.; Tassi, F.; Báez, W.; Filipovich, R.; Bustos, E.; Glok Galli, M.; Suzaño, N.; Ahumada, Ma. F.; Viramonte, J.G.; Giordano, G.; Pecoraino, G.; Vaselli, O.
Abstract: The Cerro Blanco Caldera (CBC) is the youngest collapse caldera system in the Southern Central Andes (Southern Puna, Argentina). The CBC is subsiding with at an average velocity of 0.87 cm/year and hosts an active geothermal system. A geochemical characterization of emitted fluids was carried out based on the chemical and isotopic compositions of fumaroles, and thermal and cold springs discharged in this volcanic area with the aim of constructing the first hydrogeochemical conceptual model and preliminary estimate the geothermal potential. The main hydrothermal reservoir, likely hosted within the pre-caldera basement rocks, has a Na + -Cl ˉ (HCO3 ) ˉ composition with estimated temperatures ≥135 °C. The unconsolidated, fine-grained Cerro Blanco ignimbrite likely acts as the cap-rock of the hydrothermal system. The presence of phreatic eruption breccias in the surrounding area of the geothermal fumaroles supports the effectiveness of the pyroclastic deposit as sealing rocks. The isotopic data of water (δ 18 O and δD) indicate a meteoric recharge of the hydrothermal reservoir, suggesting as recharge areas the sectors surrounding the CBC, mainly towards the W and NW where large outcrops of the pre-caldera basement exist. A fault-controlled hydraulic connection between the hot springs and the hydrothermal reservoir is proposed for the Los Hornitos area. The fumaroles show the typical compositional features of hydrothermal fluids, being dominated by water vapor with significant concentrations of H2 S, CH4 and H2 . Considering the high geothermal gradient of this area (∼104 °C/km) and the relatively high fraction of mantle He (∼39%) calculated on the basis of the measured R/Ra values, the hydrothermal aquifer likely receives inputs of magmatic fluids from the degassing magma chamber. The preliminary geothermal potential at CBC was evaluated with the Volume Method, calculating up to E = 11.4*10 18  J. Both the scarce presence of superficial thermal manifestations and the occurrence of an efficient cap-rock likely contribute to minimize the loss of thermal energy from the reservoir. The results here presented constitute the necessary base of knowledge for further accurate assessment of the geothermal potential and ultimately the implementation of the geothermal resource as a viable energy alternative for small localities or mining facilities isolated from the National Interconnected System due to their remote localization. Highlights: Compositional data of thermal fluids from the Cerro Blanco Caldera are reported. Inputs of magmatic fluids from a degassing magma chamber into the hydrothermal aquifer are inferred. Silica geothermometers indicates reservoir temperatures ≥135 °C. The local geothermal gradient for the Cerro Blanco Caldera it would be around ∼104 °C/km. The preliminary geothermal potential at Cerro Blanco Caldera has been evaluated with the Volume Method, calculating up to E = 11.4*10 18  J.